Vous êtes sur la page 1sur 9

Complex numbers

Euler’s Formula

Math 220.01, 220.02, Spring 2013

last change: Jan 15, 2013

A complex number is an expression of the form

x + iy

where x and y are real numbers and i is the “imaginary” square root of 1. For example, 2 + 3 i is a complex number. Just as we use the symbol IR to stand for the set of real numbers, we use C to denote the set of all complex numbers. Any real number x is also a

complex number, x + 0 i; that is, the set of real numbers is a subset of the set of compl ex numbers, or, in set notation, IR C .

If z = x + iy , then x is called the real part of z and y is called the imaginary part

of z . This is written

x = Re( z )

and

y = Im( z ) .

Two complex numbers are equal if and only if their real parts a re equal and their imaginary parts are equal. The conjugate of z is the complex number

z¯ = x iy

and the absolute value of z is

| z | = x 2 + y 2 .

Note that when y = 0, this is the same as the absolute value formula for real numbers x .

Note

also that, since ( x + iy )( x iy ) = x 2

i 2 y 2 = x 2 + y 2 ,

z z¯ = | z | 2 .

Complex Arithmetic

You can add, subtract, multiply, and divide complex numbers using the usual rules of algebra, keeping in mind that i 2 = 1.

Example 1:

Find the sum:

(2 + 3 i) + (4 i) = 6 + 2 i

end Example 1

Example 2:

Find the product:

(4 7 i)(2 + 3 i) =

8 14 i + 12 i 21 i 2

= 8 ( 1)21 2 i

= 29 2 i

Math 220.01, 220.02, Spring 2013 kunklet@cofc.edu, 953-5921, http://kunklet.people.cof c.edu/

Jan 15, 2013 Page 2

end Example 2

Writing a quotient in x + iy form requires the use of the conjugate, as the next example demonstrates.

Example 3:

Find the quotient:

4

7 i i = 4 7 i 2 + 3 i

2 3 i

2 + 3

i = 29 2 i = 29

4 + 9

13

2 3

2

13 i

end Example 3

The Complex Plane

Just as we think of a real number x as a point on the number line, we can think of a complex number z = x + iy as a point ( x, y ) on the plane 1 . Doing so makes for some neat geometric interpretations of complex arithmetic. For instance, if z = x + iy , then | z | = x 2 + y 2 is the distance from z to the origin. If u and v are two complex numbers, then | u v | is the distance between u and v in the complex plane. The equation | z | = 1 desribes the unit circle , that is, the circle centered at the origin with radius 1. The real number line is the x -axis, i.e., those complex numbers for which y = 0. Addition of complex numbers obeys the Parallelogram Law: the sum u + v of complex numbers u and v is the fourth vertex of the parallelogram whose other three vertices are u , v , and the origin.

| z | = 1
| z | = 1
u v
u
v

u + v

The Unit Circle.

The Parallelogram Law.

Euler’s Formula

Most of the functions with domain IR that we use in calculus ca n be meaningfully extended to the larger domain C . For polynomials and rational functions, for instance, it’ s clear how to plug in complex numbers.

Example 4: Find p(1 + 4 i)

if p( x ) = x 2 + 3 x .

1 Calculators sometimes display complex numbers in the form ( x, y ). To see how your calculator displays the complex number 2 + 3 i, enter 2 + 9.

Math 220.01, 220.02, Spring 2013 kunklet@cofc.edu, 953-5921, http://kunklet.people.cof c.edu/

Jan 15, 2013 Page 3

p(1 + 4 i) = (1 + 4 i) 2 + 3(1 + 4 i) = 1 + 8 i + 16 i 2 + 3 + 12 i = 12 + 20 i.

Example 5:

end Example 4

Evaluate r (5 2 i) if r ( x ) = ( x 1) / ( x + 2) .

r (5 2 i) = 5 2 i 1

5 2 i + 2 = 4 2 i

7 2 i

7

+ 7 + 2

2

i

i = 32

53

6

53 i.

end Example 5

But what of other functions? What could it mean, for instance, to raise e to a complex power? If we want the familiar laws of exponents to still be tr ue, then we’d need that

e x+iy = e x e iy .

We already know what e x is when x is real, but what does e iy mean? It turns out that the natural interpretation of this is given by Euler’s Formula :

(1)

e iθ = cos θ + i sin θ

(Euler is pronounced “Oil-er.”) That is, e iθ is the point on the unit circle θ radians from the positive real axis. The best explanation of why Euler’s Formula is true involves power series, a topic to be covered later in this course 2 . See page A63 of our text for a proof. In the meantime, it may be illuminating to note that Euler’s formula is consistent with two fundamental rules of trigonometry. Start with

(2)

e i(α +β ) = cos( α + β ) + i sin( α + β ) .

According to the laws of exponents, we can rewrite the left si de as

e iα e iβ = (cos α + i sin α )(cos β + i sin β )

(3)

= cos α cos β sin α sin β + i(cos α sin β + sin α cos β )

Equating real and imaginary parts of (2) and (3), we see

(4)

cos( α + β ) = cos α cos β sin α sin β, and

sin( α + β ) = cos α sin β + sin α cos β,

2 Power series also allow us to define f ( x + iy ) for many familiar functions f ( x ).

Math 220.01, 220.02, Spring 2013 kunklet@cofc.edu, 953-5921, http://kunklet.people.cof c.edu/

Jan 15, 2013 Page 4

the sum formulas for sine and cosine. Euler’s formula allows us to rewrite exponentials in terms o f trigonometric functions. It is also useful to be able to go the other way: write trigonom etric functions in terms of exponentials. To derive the necessary formula, note that , since cos( θ ) = cos θ and sin( θ ) = sin θ ,

e iθ = cos θ + i sin θ

and

e iθ = cos θ i sin θ.

That is, e iθ and e iθ are conjugates 3 . By adding or subtracting these equations, and dividing by 2 or 2 i, we obtain the desired formulas:

e iθ + e −iθ (5) = cos θ e iθ − i e −iθ
e iθ + e −iθ
(5)
= cos θ
e iθ − i e −iθ = sin θ
2
2

Note the similarity to the definitions of cosh and sinh 4 . Using equations (1) and (5) often makes it unnecessary to rem ember tricks involving trigonometric identities. We next look at two examples of indefinite integrals that, without Euler’s formula, would require use of the sum and difference formulas for sine and cosine.

Example 6: Integrate: sin 2 x dx . Before integrating, it is necessary to rewrite the integrand. By (5),

Now we can integrate:

e ix e ix

2

i

2

sin 2 x =

1

=

4

1

=

4

sin 2 x dx =

=

=

( e i2 x + e i2 x 2 e 0 )

(2 cos 2 x 2) .

1 (2 cos 2 x 2) dx

4

1

4

1

4

(sin 2 x 2 x ) + C

1

sin 2 x + 2 x + C.

(Compare with the solution in Example 3, page 461, which uses the half-angle identities.)

end Example 6

3 Another familiar trigonometry formula follows from these two equations:

cos 2 θ + sin 2 θ = (cos θ + i sin θ )(cos θ i sin θ ) = e iθ e iθ = e 0 = 1 .

4

Equations (5) are special cases of the formula z +¯z = Re( z ) and z z¯ = Im( z ) .

2

2

i

Math 220.01, 220.02, Spring 2013 kunklet@cofc.edu, 953-5921, http://kunklet.people.cof c.edu/

Jan 15, 2013 Page 5

Example 7: Integrate: sin 4 x cos 5 x dx . The integrand can be rewritten as a sum of sine functions. Sta rt with (5):

sin 4 x cos 5 x = e i4 x e i4 x

2

i

e i5 x + e i5 x

2

e i9 x e i9 x e ix + e ix

=

=

=

4 i

1

e i9 x e i9 x

2 i

2

1

2 (sin 9 x sin x ) .

e ix e ix

2

i

Now integrating is straightforward:

sin 4 x cos 5 x dx = 1 2 (sin 9 x sin x ) dx

= 1

18

1

cos 9 x + 2 cos x + C

(Compare with the solution in Example 9, page 465, which reli es on the three identities on that page.)

end Example 7

Generally, when presented with an integral of the form

(6)

sin αx sin βx dx

sin αx cos βx dx

cos αx cos βx dx

or

(7)

sin n x cos m x dx

you can use either trigonometric identities as in §7.2 or Euler’s formula to rewrite the integrand so as to make the integration simple. (When either n or m is odd, it’s easier to integrate (7) with a substitution as in §7.2.)

Pascal’s Triangle

For integrals of the last kind, it is helpful to be able to quickly expand powers of the form ( x + y ) n . The expansion must look something like

( x + y ) n =?x n +?x n1 y +?x n2 y 2 + · · · +?x 2 y n2 +?xy n1 +?y n .

Setting x or y equal zero tells us that the first and last coefficients must bot h be 1, but what about the others?

Math 220.01, 220.02, Spring 2013 kunklet@cofc.edu, 953-5921, http://kunklet.people.cof c.edu/

Jan 15, 2013 Page 6

It turns out that these numbers, called the binomial coefficients, are found in the n th row of Pascal’s Triangle :

 

1

 

1

1

 

1

2

1

1

3

3

1

(Pascal’s Triangle has infinitely many rows. We refer to the t op row as its 0th row.) For instance, the 2nd row, “1 2 1,” and the 3rd row, “1 3 3 1,” tell us that

( x + y ) 2

( x + y ) 3 = x 3

= x

2

+ 2 xy + y 2 , and

+ 3 x 2 y + 3 xy 2 + y 3 .

To generate the next row, begin and end with a 1, and then add the two elements above to find the next entry. For example, since 1+3 = 4, the next row w ill begin

1

 

1

1

 

1

2

1

 

1

3

3

1

1

4

1

Finish the row with the sums 3 + 3, and 3 + 1:

 
 

1

 

1

1

 

1

2

1

 

1

3

3

1

1

4

6

4

1

Consequently,

( x + y ) 4 = x 4 + 4 x 3 y + 6 x 2 y 2 + 4 xy 3 + y 4 .

To see why this works, consider the problem of expanding ( x + y ) 3 . You could find ( x + y ) 3 by multiplying ( x + y ) 2 by ( x + y ):

( x + y ) 3 =

( x 2 + 2 xy + y 2 )( x + y )

=

x

3

+ 2 x 2 y + xy 2

 

+ x 2 y

+ 2 xy 2 + y 3

=

x

3

+ 3 x 2 y + 3 xy 2 + y 3 .

Similarly, you could find ( x + y ) 4 by multiplying ( x + y ) 3 by ( x + y ):

( x + y ) 4

=

( x 3 + 3 x 2 y + 3 xy 2 + y 3 )( x + y )

=

x

4

+ 3 x 3 y + 3 x 2 y 2 + xy 3

 

+ x 3 y + 3 x 2 y 2 + 3 xy 3 + y 4

 

=

x

4

+ 4 x 3 y

+ 6 x 2 y 2

+ 4 xy 3 + y 4 .

Math 220.01, 220.02, Spring 2013 kunklet@cofc.edu, 953-5921, http://kunklet.people.cof c.edu/

Jan 15, 2013 Page 7

Notice that each coefficient in the expansion of ( x + y ) 3 or of ( x + y ) 4 , with the exception of the beginning and ending 1s, is the sum of the two neighbori ng coefficients in the row above. When we use one row to generate the next, we’re just per forming this process without all the symbols.

Example 8:

Integrate: cos 6 x dx .

To simplify the integrand in cos 6 x dx , first use Euler’s formula:

cos 6 x = e ix + e ix

2

6

.

After some addition, we find the 6th row of Pascal’s Triangle t o be

1

6

15 20 15

6

1

and so

e ix + e ix

2

6

1

= 64 e i6 x + 6 e i4 x + 15 e i2 x + 20 + 15 e i2 x + 6 e i4 x + e i6 x

1

= 32 (cos 6 x + 6 cos 4 x + 15 cos 2 x + 10)

Now we can integrate: cos 6 x dx = 32 1 6 sin 6 x +

1

3

2

sin 4 x + 15

2

sin 2 x + 10 x + C .

end Example 8

Example 9:

Integrate: cos 4 x sin 4 x dx .

Use Euler’s formula to rewrite the integrand:

cos 4 x sin 4 x = e ix + e ix

2

4 e ix e ix

2

i

4

.

The 4th row of Pascal’s Triangle is 1

4

6

4

1 , so

e ix + e ix 4 e ix e ix

2

2

i

4

= 1

2

8 e i4 x + 4 e i2 x + 6 + 4 e i2 x + e i4 x e i4 x 4 e i2 x + 6 4 e i2 x + e i4 x

Next, carefully multiply out this product.

1

8 ( e i8 x + 4 e i6 x + 6 e i4 x + 4 e i2 x + 1

2

4 e i6 x 16 e i4 x 24 e i2 x 16 4 e i2 x

+ 6 e i4 x + 24 e i2 x + 36 + 24 e i2 x + 6 e i4 x

4 e i2 x 16 24 e i2 x 16 e i4 x 4 e i6 x

Math 220.01, 220.02, Spring 2013 kunklet@cofc.edu, 953-5921, http://kunklet.people.cof c.edu/

Jan 15, 2013 Page 8

Collect up like terms, and the integrand is

1

= 8 e i8 x 4 e i4 x + 38 4 e i4 x + e i8 x

2

7 e i8 x + e i8 x 4 ( e i4 x e i4 x )
=

1

2

2

2

= 1 7 (cos 8 x 4 cos 4 x + 19)

2

+ 19

which is straightforward to integrate. The integration is l eft to the reader.

end Example 9

It helps to keep on eye out for times when the integrand can be simplified using the double angle formulas or the pythagorean identities. For instance, let’s look once more at the integral from the previous example.

Example 10:

This particular integral can be made a lot easier by first using the double angle formula for sine: sin 2 x = 2 sin x cos x . Rewrite the integrand as

Integrate: cos 4 x sin 4 x dx .

1

cos 4 x sin 4 x = ( 1 2 sin 2 x ) 4 = 16 sin 4 2 x

and then substitute u = 2 x (so that 1 2 du = dx ). The integral then becomes 32 sin 4 u du .

1

end Example 10

Math 220.01, 220.02, Spring 2013 kunklet@cofc.edu, 953-5921, http://kunklet.people.cof c.edu/

Jan 15, 2013 Page 9

Exercises

1. Write in x + iy form:

a.

d.

g.

3 + 2 i + 2(1 i)

1

(6 + 3 i)( 3 2 i)

e iπ/ 4

b. 3(4 5 i) (2 4 i)

e. (4 + i) ÷ (1 8 i)

h.

e 5 iπ/ 6

c. ( i + 1)( i 1) (3 + 2 i) ÷ 2(1 i)

f.

i.

e 2 3 i

2. Two Facts about Complex Arithmetic. If z = x + iy and u = a + ib , then prove that u + z = u¯ + z¯. That is, the conjugate of the sum is the sum of the conjugates. Prove also that uz = u¯ z¯. That is, the conjugate of the product is the product of the co njugates.

3. Plot 0, u , v , and u + v in the complex plane. Compare with Parallelogram Law.

a. u = 3 + 2 i, v = 2 i

b. u = 1 + i, v = 1 + 2 i

c.

u = 1 , v = 2 i

4. Plot z and z¯. In general, how are z and z¯ related geometrically?

a.

z = 4 + 2 i

b. z = 1 2 i

c. z = 3

5. Plot the solution set: it might help you to first write the eq uation in terms of x and y , the real and imaginary parts of z .

a.

| z | = 2

b.

| z 1 | = 1

c. | z 1 + i| = 1 / 2

6. Arrive at the formulas for cos 2 θ and sin 2 θ from (1) by squaring, and again from (4) by a substitution.

7. Prove DeMoivre’s formula: (cos θ + i sin θ ) n = cos + i sin .

d

d

8. Use (5) to “derive” the rules dx sin x = cos x and dx cos x = sin x .

9. Use Pascal’s Triangle to expand the binomial:

a.

e.

( x + y ) 7

a +

1

a 9

10. Integrate:

b. ( x y ) 7

c. ( x y ) 8

f. ( e x e x ) 9

g. (1 v 2 ) 8

d.

h.

a

( u 2 + 1) 9

1

a 8

a.

d.

g.

j.

m.

sin 3 x sin 5 x dx

sin 4 x dx

cos 2 x sin 2 x dx

cos 4 x dx

π/ 2

0

cos 8 x dx

b. cos 2 x cos 4 x dx

e. sin 6 x dx

h.

k.

n.

cos 4 x sin 4 x dx

cos 3 x cos 5 x dx cos 4 x sin 2 x dx

Selected Answers

π

0

c.

sin 2 x cos 4 x dx

f. sin 2 x cos 2 x dx

i. cos 2 x sin 2 x dx

l.

π/ 4

0

cos 2 x sin 2 x dx

o.

tan 4 x sec 4 x

dx

1.

5.

( e iθ ) n = e inθ = cos + i sin .

b. 10 11 i; c. 2 ; f. 1

2 i; i. e 2 cos 3 ie 2 sin 3 . 4. ¯z is the reflection of z across the real axis.

a. circle of radius 2 , centered at origin. c. circle of radius 1 2 , centered at (1 , 1) . 7. (cos θ + i sin θ ) n =

9. b. x 7 7 x 6 y + 21 x 5 y 2 35 x 4 y 3 + 35 x 3 y 4 21 x 2 y 5 + 7 xy 6 y 7 ; d.

4 + 4 i; h. 2 3

5

1
1

a 8 8 a 6 + 28 a 4

56 a 2 + 70 56 a 2

+ 28 a 4 8 a 6 + a 8 ; f. e 9 x 9 e 7 x

+ 36 e 5 x 84 e 3 x + 126 e x 126 e x +

84 e 3 x 36 e 5 x

+ 9 e 7 x e 9 x . h.

u 18 + 9 u 16 + 36 u 14 + 84 u 12 + 126 u 10 + 126 u 8 + 84 u 6 + 36 u 4 + 9 u 2 + 1 . 10. a.

4 sin 2 x 16 sin 8 x + C ; c. 4 cos 2 x 12 cos 6 x + C ; d.

1

1

1

1

1

8 (

1

4

sin 4 x 2 sin 2 x + 3 x ) + C ; e. 192 sin 6 x + 64 sin 4 x

1

3

64 sin 2 x + 16 x + C ; f. 8 x 32 sin 4 x + C . g. sin x cos x + C ; h. same as g.; i. 8 cos 4 x + C j. 3 π/ 8 ; k. 0; l.

15

5

1

1

1

π/ 32 ; m.

1

7 (

2

8 sin 8 x + 4 sin 6 x + 7 sin 4 x + 27 sin 2 x + 70 x ) + C ; n.

1

3

5 ( 1 6 sin 6 x 2 sin 4 x + 2 sin 2 x + 4 x ) + C ;

2

1

1

1